Presentation Secrets of Steve Jobs: Draw a Roadmap Using the Rule of Three - Gallo, Carmine (McGraw-Hill's AccessEngineering., 2011)
Learn to draw a verbal road map for your audience, a preview of coming attractions, to help your listeners follow the story. Understand why these road maps should be outlined in groups of three.